1996
DOI: 10.1038/nbt1196-1570
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus targeted to heparan-containing receptors increases its gene delivery efficiency to multiple cell types

Abstract: Adenovirus (Ad) is used as a vector for gene delivery in therapies involving genetic disease, vascular disease, and cancer. The first step for efficient gene transfer is effective virus binding to the target cells. We have found that Ad-mediated gene delivery to multiple cell types is much less efficient compared to epithelial-derived cells. Low gene delivery to nonepithelial cell types was directly correlated to a deficiency of the cellular receptor which mediates Ad binding. To overcome this inefficiency we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
221
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 301 publications
(229 citation statements)
references
References 18 publications
8
221
0
Order By: Relevance
“…Other investigators have genetically modified the adenovirus to include new binding motivs into the viral capsid 11 or the HI loop. 12 In these studies, the native binding to the CAR receptor was not blocked, and therefore vector tropism was not changed; additional tropism was added in these instances.…”
Section: Figure 3 Selective Infection Of Human Colorectal Cancer Cellmentioning
confidence: 99%
“…Other investigators have genetically modified the adenovirus to include new binding motivs into the viral capsid 11 or the HI loop. 12 In these studies, the native binding to the CAR receptor was not blocked, and therefore vector tropism was not changed; additional tropism was added in these instances.…”
Section: Figure 3 Selective Infection Of Human Colorectal Cancer Cellmentioning
confidence: 99%
“…However, there is growing evidence that the expression of CAR is frequently suppressed in various types of cells, including tumor cells and in primary tumors [4,5], resulting in resistance to adenovirus infection [6][7][8]. Nevertheless, various studies have shown that adenovectors with modified capsid proteins, such as additions of polylysine or RGD sequence to fibers, can effectively infect cells with defective CAR expression [9][10][11]. Thus, modified adenovectors with increased transduction ability or targeting capacity may be useful for various gene transfer or gene therapy studies or clinical applications.…”
mentioning
confidence: 99%
“…Although ligands fused to the C terminus of the fiber molecule can physically interact with cognate cellular receptors, the C terminus of fiber can only accommodate ligands up to 30 aa in size, other than the non-structured biotin acceptor protein. 75,78,79 Alternatively, small ligands such as FLAG, RGD, polylysine and transferrin receptor binding peptides can be incorporated into the highly flexible HI loop of fiber. [31][32][33][34] Belousova and co-workers 37 have recently demonstrated the capacity of the HI loop to accommodate large (480 aa) targeting ligands by successfully generating infectious virions containing fragments of the penton base RGD loop inserted into the HI loop.…”
Section: Discussionmentioning
confidence: 99%